Differences in Halal Food Knowledge and Providing Flashcard and Leaflet Media Education to Students - kharisma imami; Endah Budi Permana Putri (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2023)
Halal food is important for the Muslim community, halal certification of a food or beverage product needs to be done to ensure the public that the product being consumed has proven its halalness. Therefore, it is very important as a Muslim community to increase halal food knowledge. This study aims to determine the difference in halal food knowledge by providing education with Flashcard and Leaflet media to FKIP students at Nahdlatul Ulama University Surabaya. The method of this study was True Experimental Design using Pre-Post Test Design. The sample in this study amounted to 66 respondents. Sampling in this study using Simple Random Sampling technique. Then divided into 33 respondents in the Intervention group and 33 respondents in the control group. The test analysis used was the Mann Whitney test with a significant level (α=0.05). The results showed that there were differences in the respondents' knowledge in the group that was given leaflet media education and in the group that was given flashcard media education with the result (p=0.029). It is hoped that there will be more research using other methods in increasing more knowledge of halal food